2005
DOI: 10.1002/ptr.1721
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of chromatographic fractions ofPhyllanthus amarus on the serum biochemistry of rats

Abstract: Chromatographic fractions obtained from Phyllanthus amarus were tested for toxicity on the serum biochemistry of rats. The results revealed that some fractions of P. amarus had potentially deleterious effects on the blood and therefore caution should be exercised in the use of P. amarus as a medicinal plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
1
15
1
Order By: Relevance
“…Oral gavage of increasing concentrations of Moringa peregrina leaves ethanolic extracts for six days to mice significantly increased total WBCs numbers in the peripheral blood. Similar results were obtained with Moringa oleifera leaves ethanolic extract [ 8 , 9 ]. Such leucopoiesis effect could enhance immune response towards infectious agents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Oral gavage of increasing concentrations of Moringa peregrina leaves ethanolic extracts for six days to mice significantly increased total WBCs numbers in the peripheral blood. Similar results were obtained with Moringa oleifera leaves ethanolic extract [ 8 , 9 ]. Such leucopoiesis effect could enhance immune response towards infectious agents.…”
Section: Discussionsupporting
confidence: 89%
“…Pre-treatment with Moringa extract inhibited cyclophosphamide bone marrow suppressive effect on phagocytic activity in mice [ 8 ]. Furthermore, various doses of Moringa oleifera caused a significant increase in the level of white blood cell counts and immunoglobulin levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The animals in the controlled experiment received only distilled water for the same number of days. The results revealed that some fractions of P. amarus had potentially deleterious effects on the blood and caused a significant increase in level of ALT, ALP, total bilirubinand blood urea nitrogen when compared with control (Adedapo et al, 2005a). The aqueous crude extract was administered orally to male rats of the Sprague Dawley strain in three groups receiving doses of 400, 800 and 1000 mg/kg but the fourth group served as a control and received distilled water only.…”
Section: Toxicological Assessment and Contraindicationsmentioning
confidence: 98%
“…Body weight change of animals was also assessed, since changes in the body weights can be used as an indicator of adverse or toxic effects of drugs [ 16 , 17 ]. In this study, it was observed that the change in body weight of animals treated with the extract was not significant when compared to the control group, indicating absence of any severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%